2016
DOI: 10.1371/journal.pone.0166495
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Renal Hyperfiltration and the Sources of Habitual Protein Intake and Dietary Acid Load in a General Population with Preserved Renal Function: The KoGES Study

Abstract: Although the differential response of the kidney to the acute load of various sources of dietary protein in subjects with normal renal function is well known, the influence of habitual dietary protein intake and dietary acid load on renal function has not been tested well. The association between renal hyperfiltration (RHF), the earlier and possibly reversible stage of chronic kidney disease, and the sources of habitual dietary protein and dietary acid load was analyzed with the baseline data of 123,169 middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
2
8
0
1
Order By: Relevance
“…Dietary acid load (estimated net endogenous acid production) was positively correlated with animal protein intake and inversely correlated with vegetable protein intake, as expected. Dietary acid load was positively associated with glomerular hyperfiltration in all participants, irrespective of sex and age (So et al, 2016). Consistently, an association between lower serum bicarbonate (reflecting increased dietary acid load due to animal protein intake) and higher odds of renal hyperfiltration has been observed in 41,886 adults with normal kidney function (estimated GFR > 60 ml/min/1.73 m 2 , calculated with the CKD-EPI-creatinine equation) from the general population (Park et al, 2016).…”
Section: Glucagon Secretion Elicited By Animal Protein Ingestion Caussupporting
confidence: 59%
“…Dietary acid load (estimated net endogenous acid production) was positively correlated with animal protein intake and inversely correlated with vegetable protein intake, as expected. Dietary acid load was positively associated with glomerular hyperfiltration in all participants, irrespective of sex and age (So et al, 2016). Consistently, an association between lower serum bicarbonate (reflecting increased dietary acid load due to animal protein intake) and higher odds of renal hyperfiltration has been observed in 41,886 adults with normal kidney function (estimated GFR > 60 ml/min/1.73 m 2 , calculated with the CKD-EPI-creatinine equation) from the general population (Park et al, 2016).…”
Section: Glucagon Secretion Elicited By Animal Protein Ingestion Caussupporting
confidence: 59%
“…Proteinuria was defined as spot urine dipstick test for protein 1+ or higher and incident proteinuria as conversion of spot urine dipstick test, negative at the individual’s first health screening to 1+ or higher at any time during the follow-up period. RHF was defined as previously proposed with some modifications [ 11 , 27 ] by using initial health screening data of each participant. Briefly, the residuals were calculated from a multiple linear regression analysis, in which the logarithm-transformed eGFR was a dependent variable and sex, weight, height, known history of medication for diabetes and/or hypertension, and logarithm-transformed age were independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Renal hyperfiltration (RHF) has long been considered as one of the mechanisms of the progression of chronic renal diseases after a certain degree of renal injury has developed [ 1 ]. RHF has been associated with various clinical conditions including pre-diabetes and diabetes, pre-hypertension and hypertension, and metabolic syndrome [ 2 – 6 ], as well as lifestyle factors like obesity, smoking, lack of physical activity, lower cardiopulmonary fitness, and increased dietary acid load mainly due to a Western-style diet [ 7 – 11 ]. The clinical implications of RHF are not yet clear in conditions other than diabetes, in which RHF is considered as one of the initiating mechanisms of renal complications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In two large population-based studies from community-dwelling elderly Koreans (KoGES), increasing NEAP and low-normal HCO 3 − is associated with subclinical acidosis and CKD [ 29 , 30 ]. Consistently, acid loading in a number of studies has been shown to be associated with proteinuria, progressive reduction of eGFR and development of CKD [ 31 , 32 , 33 , 34 ].…”
Section: Maladaptations To the Modern Diet And Health Implicationsmentioning
confidence: 99%